2018
DOI: 10.2139/ssrn.3312153
|View full text |Cite
|
Sign up to set email alerts
|

Performance under Pressure on the Court: Evidence from Professional Volleyball

Abstract: This study analyzes how psychological pressure affects performance. It refers to the discussion on differences between choking, i.e., an acute performance decline under pressure and underperformance under pressure. When performance outcomes are not defined binary even slight performance decrements can have huge consequences for future career. To study the consequences of psychological pressure on performance, we employ data on the serving performance of 213 professional volleyball athletes in 226 matches. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Considering the percentage of positive serves among jump power serves to the libero (Table 5), we can see that in 2021 the share of positive serves was greater than in the earlier year, and more points were gained after both negative (35%) and positive serves (48%). Timeouts lower considerably the performance of the serving player, decreasing the proficiency of the serve and gaining of direct points [2]. The current study revealed that, in the tournament of 2021, the players erred more after timeouts than in the tournament of the earlier year (Table 6).…”
Section: Resultsmentioning
confidence: 48%
“…Considering the percentage of positive serves among jump power serves to the libero (Table 5), we can see that in 2021 the share of positive serves was greater than in the earlier year, and more points were gained after both negative (35%) and positive serves (48%). Timeouts lower considerably the performance of the serving player, decreasing the proficiency of the serve and gaining of direct points [2]. The current study revealed that, in the tournament of 2021, the players erred more after timeouts than in the tournament of the earlier year (Table 6).…”
Section: Resultsmentioning
confidence: 48%
“…A twister or a lob would be a risky throw. Likewise,Bozhinov and Grote (2018) use the jump serve as a proxy for risk taking in volleyball.…”
mentioning
confidence: 99%